Impact of board independence on the quality of community disclosures in annual reports - Yekini, Kemi C.; Adelopob, Ismail; Andrikopoulos, Panagiotis (Elsevier, 2015)
This study investigates the link between board independence and the quality of community disclosures in annual reports. Using content analysis and a panel dataset from UK FTSE350 companies the results indicate a statistically significant relationship between board independence, as measured by the proportion of nonexecutive directors, and the quality of community disclosures, while holding constant other corporate governance and firm specific variables. The study indicates that companies with more non-executive directors are likely to disclose higher quality information on their community activities than others. This finding offers important insights to policy makers who are interested in achieving optimal board composition and furthers our understanding of the firm’s interaction with its corporate and extended environment through high-quality disclosures. The originality of this paper lies in the fact that it is the first to specifically examine the relationship between outside directors and community disclosures in annual reports. The paper contributes both to the corporate governance and community disclosure literature.